Gambaran Rasionalitas Pengobatan Antibiotik pada Pasien Poli Gigi berdasarkan Metode Gyssens di Rumah Sakit Intan Husada Garut - Nurul; Sifa Nurhasanah, Sifa (Jurnal Medika Farmaka, 2025)
practice. Antibiotics are frequently prescribed to support surgical procedures, manage acute inflammation, treat infections, and prevent systemic complications. However, prescriptions are not always based on clinical guidelines or rational considerations. This study aimed to evaluate the rationality of antibiotic use among dental patients at Intan Husada Hospital, Garut, using the Gyssens method. A descriptive quantitative design was applied by reviewing medical records of patients who received antibiotics in December 2024. The Gyssens method classifies prescriptions from category 0 (rational) to category VI (not evaluable due to incomplete data). Out of 58 patients, none of the prescriptions were categorized as 0, indicating 0% rational use. Most prescriptions (89.66%) fell into category IVC, reflecting a lack of consideration for cheaper but equally effective generic alternatives. The remaining 10.34% were classified as IIIB due to prolonged duration of therapy. These findings highlight that irrationality was not primarily related to clinical indications but rather to cost-efficiency aspects. Previous studies confirmed that generic antibiotics, including amoxicillin, are therapeutically equivalent to branded drugs. Strengthening education and implementing policies that encourage the use of generic antibiotics are essential strategies to promote more rational therapy in dental healthcare services